Analisis Faktor Faktor yang Mempengaruhi Penyerapan Tenaga Kerja di Eks Karesidenan Surakarta Tahun 2006 2013 - Cahyono, Apri; , Eny Setyowati.,SE.,MSi (2016)
This study analyzes the effect of the minimum wage, the gross regional domestic product and inflation on employment in Surakarta residency years 2006-2013. The analytical method used is the panel data regression. Panel data in this study is a combination of cross section data are seven districts / cities in karesiden Surakarta and times series for depalan years from 2006-2013. The results of this study indicate that the Fixed Effects Model (FEM) is the best model. Based on the regression results, together variable minimum wage, the gross regional domestic product and inflation mempengaruhipenyerapan labor in Surakarta residency years 2006-2013. Partially, variable minimum wage and inflation significant negative effect on employment, while gross domestic product regionally significant positive effect on employment.